Fenomena Fatherlessness dalam Perspektif Tafsir Al-Misbah dan Teori Keterlibatan Ayah Michael Lamb - Hidayati, Lailatun Nuzula; Sugiarto, Fitrah (Peradaban Journal of Religion and Society, 2025)
The phenomenon of fatherlessness, defined as the absence of a father's role in a child's life, poses a serious challenge in the modern era. Its impacts include weakened self-control, diminished quality of social relationships, and identity crises in children. This pervasive gap highlights the urgent need to revitalize the father's role, not merely as a material provider, but also as an essential educator and spiritual guide. This research aims to examine the concept of fatherly exemplary behavior as presented in Surah Ash-Shaffat [37]: 102 through Tafsir al-Misbah and integrate it with Michael E. Lamb's theory of father involvement, which encompasses the dimensions of engagement, accessibility, and responsibility. The study employs a descriptive qualitative method utilizing a library research approach and content analysis techniques applied to tafsir texts, Islamic literature, and child developmental psychology theories. The findings indicate that Prophet Ibrahim's exemplary guidance of Ismail reflects ideal fatherly involvement, characterized by dialogical communication, a secure emotional presence, and role modeling in fulfilling spiritual responsibilities. This integration demonstrates that Quranic values align significantly with modern psychological findings, providing a robust conceptual basis for developing a balanced family education model that judiciously incorporates both religious and scientific aspects. Fenomena fatherlessness atau ketidakhadiran peran ayah dalam kehidupan anak merupakan persoalan serius di era modern. Dampaknya m1encakup lemahnya kontrol diri, penurunan kualitas hubungan sosial, hingga krisis identitas pada anak. Kesenjangan ini menunjukkan urgensi untuk merevitalisasi peran ayah, tidak hanya sebagai penyedia kebutuhan material, tetapi juga sebagai pendidik dan pembimbing spiritual. Penelitian ini bertujuan untuk mengkaji konsep keteladanan ayah dalam Surah Ash-Shaffat [37] : 102 melalui Tafsir al-Misbah dan mengintegrasikannya dengan teori keterlibatan ayah menurut Michael E. Lamb, yang mencakup dimensi engagement, accessibility, dan responsibility. Metode yang digunakan adalah kualitatif deskriptif melalui pendekatan kepustakaan (library research), dengan teknik analisis isi terhadap teks tafsir, literatur keislaman, dan teori psikologi perkembangan anak. Hasil penelitian menunjukkan bahwa keteladanan Nabi Ibrahim dalam membimbing Ismail mencerminkan keterlibatan ayah yang ideal: komunikasi dialogis, kehadiran emosional yang aman, dan keteladanan dalam menjalankan tanggung jawab spiritual. Integrasi ini menunjukkan bahwa nilai-nilai Al-Qur’an sejalan dengan temuan psikologi modern, dan dapat menjadi dasar konseptual untuk membangun model pendidikan keluarga yang berimbang antara aspek religius dan ilmiah.